Vibration analysis of thermally buckled SMA hybrid composite sandwich plate. (January 2015) - Samadpour, M.; Sadighi, M.; Shakeri, M.; Zamani, H.A.
Abstract: Nonlinear free vibration of thermally buckled sandwich plate with embedded pre-strained shape memory alloy (SMA) fibers in temperature dependent laminated composite face sheets is investigated. The one-dimensional Brinson model is employed for recovery stress generated during phase transformation of the pre-strained SMA fibers. Nonlinear equations of motion of sandwich plate are derived based on the first-order shear deformation theory and von Karman geometric nonlinearity via Hamilton principle. The Galerkin weighted residual method is utilized to obtain buckling temperature and fundamental natural frequency. Extensive numerical results are depicted to provide an insight into the effects of pre-strain, volume fraction and location of the SMA fibers, lamination scheme and geometrical parameters on the dynamic behavior of sandwich plates. Results reveal that SMA fibers have a significant effect on the natural frequency and post-buckling deflection due to recovery stress generation. Due to the absence of similar results in the literature, this paper is likely to fill a gap in the state of the art of this problem.